Studies on Antimicrobial Activity of Marine Actinomycetes Isolated from Rameswaram - K Nirmal Kumar, Dr (International Journal of Pharmaceutical & Biological Archive, 2014)
Studies on Antimicrobial Activity of Marine Actinomycetes Isolated from Rameswaram